PENGARUH SRATEGI, PRODUK, HARGA, DAN LOKASI TERHADAP PERSAINGAN BISNIS DI NAIMA SALON BENGKONG - Bu’ulolo, Asnadayanti; Susanthi, Putu Rani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2025)
From the results of research that has been carried out on marketing strategies in the salon industry in an effort to increase income and improve through observation, interviews, documentation, literature studies and competitor studies, it can be concluded as follows: There is an influence of strategy, product, price and location on business competition at Naima Salon has had a big impact on the development of the salon business. In addition, satisfied customers are able to encourage business development through harmonizing suggestions or input to Naima Salon to improve product and service quality. Apart from that, Naima Salon is also aware of the important role of digital technology in increasing Naima Salon customers by providing information in the form of promotions, discounts and so on. After conducting observations and analysis, the obstacle that Naima Salon experienced was people’s income falling, so to overcome this, Naima Salon opened salon classes, both online and offline